Microcrédito e bancarização no Brasil de 1995 a 2013 - Lima, Fernanda Maria Nogueira (2018)
The purpose of this study was to analyze the granting of microcredit in Brazil in the period 1995-2013 comparing the Brazilian experience with the experience of Bangladesh. In the last decades it has been observed a substantial advance in the financial market with the development of several tools that contribute to the increment of the current economic scenario. This evolution, over time, has promoted a national economic development, besides contributing to the reduction of unemployment and informality in companies. However, there is still a large gap between the low-income population and the tools available, as it is possible to observe that the high cost of credit operations for the population, mainly due to the lack of real guarantees, costs of these operations, resulting in an obstacle to obtaining credit in Brazil and consequently the financial inclusion of this population. Banking is one of the possible mechanisms to insert the low income population in the banking system and to promote a regulatory form that allows these people to obtain access to a subsidized credit, enabling entrepreneurship, the release of resources for investment and working capital, resulting in in obtaining credit with sustainability and contributing to the financial inclusion and citizenship of the most disadvantaged classes. In the course of this endeavor, the most successful experience, both in practical terms and in theoretical terms, is the case of Bangladesh, which served as a scope to verify why it persisted for several periods and economic policies and even with several governments in different periods, such as the 1995-2013 period, it was noted that the intentions were frustrated and did not make significant progress. Based on the Microcredit Revolution, the successful case of Bangladesh and the Brazilian experience were compared, since they are countries with similar initiatives of financial inclusion, public services of insufficient quality and with still anachronistic problems in socioeconomic indicators. It is concluded that despite being in the process of improvement, it has not yet promoted the social inclusion expected due to the high costs. Therefore, the results are heterogeneous, where some segments show improvement, and others, such as those of extreme poverty, microcredit further aggravates the situation, promoting inability to pay and consequent indebtedness